2019
DOI: 10.1002/wsb.1021
|View full text |Cite
|
Sign up to set email alerts
|

Comparing methods of estimating carnivore diets with uncertainty and imperfect detection

Abstract: Carnivore diet‐selection studies based on scat analyses are frequently used to elucidate predator ecology, predict potential effects on prey populations, and inform management decisions. However, accuracy of results and the following inference are contingent on multiple sources of sampling error including missed detections and pseudoreplication in statistical comparisons that assume independence within scat samples. We compared a repeated‐sampling occupancy framework intended to estimate detection and occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…meta-barcoding) may reduce sources of bias in some cases. For example, Morin et al (2019) found that detectability can vary among food items when using morphometrics, for example, deer hair can dominate a sample and obscure the presence of small mammal hair.…”
Section: Limitationsmentioning
confidence: 99%
“…meta-barcoding) may reduce sources of bias in some cases. For example, Morin et al (2019) found that detectability can vary among food items when using morphometrics, for example, deer hair can dominate a sample and obscure the presence of small mammal hair.…”
Section: Limitationsmentioning
confidence: 99%
“…Sometimes, when empirical data on sensitivity was not available through controlled conditions, statistical approaches were used to account for false‐positive and false‐negative errors (Chambert et al, 2015; Lahoz‐Monfort et al, 2016). Detection probability of DNA methods has been indirectly estimated with capture‐mark‐recapture or occupancy modeling for species detection from eDNA samples (Abrams et al, 2019; Broadhurst et al, 2021; Sales et al, 2020; Smith & Goldberg, 2020), as well as for prey detection in predator scats (Morin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This also highlights that DNA degradation can happens quite fast despite samples being in a cold environment. Again, this emphasizes the need to collect feces as fresh as possible and to set correction metrics and models for false negative or imperfect detection (Alberdi et al, 2019;Monterroso et al, 2019;Morin et al, 2019).…”
Section: Joint Use Of Morphological and Molecular Dietary Analysesmentioning
confidence: 99%
“…Qualitative estimates such as frequency of occurrence are also useful to document the range of potential food sources for a given species (Klare et al, 2011). Independently of the metrics used, dietary estimates derived from morphological analyses could be biased by differential digestibility of food items and low occurrence of certain food sources resulting in false negatives or unidentifiable items (Morin et al, 2019;Steenweg et al, 2015). For instance, although behavioral observations often reveal predation by rodents on the eggs of seabirds, it is difficult to accurately assess the importance and occurrence of this food source because eggshells and yolk rarely leave remains in feces of rodents (Drever, Blight, Hobson, & Bertram, 2000).…”
Section: Introductionmentioning
confidence: 99%